2018
DOI: 10.1007/s11356-018-1353-3
|View full text |Cite
|
Sign up to set email alerts
|

UV modification of biochar for enhanced hexavalent chromium removal from aqueous solution

Abstract: This study was conducted to understand the effects of ultraviolet (UV) irradiation on the physicochemical properties and the hexavalent chromium (Cr(VI)) removal ability of biochar. Structural and morphological analysis showed that UV irradiation increased the specific surface area of biochar and added a large amount of oxygen-containing functional groups (e.g., carboxyl, lactonic, and hydroxyl) to biochar's surface. Batch sorption experimental results showed that UV-modified biochar (UVBC) produced at the pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…However, the pristine biochars, acquired from direct biomass pyrolysis, often have relatively low adsorptive and reductive ability for Cr(VI), but these properties are dependent on biomass feedstock and pyrolysis temperature (Dong et al, 2011;Jin et al, 2016;Zhang et al, 2018). Thus, specific activation processes, such as surface functionalization, molecular grafting, ultraviolet irradiation and ball milling, have been used to enhance the Cr(VI) removal performance of biochars (Peng et al, 2018;Zhang et al, 2019b;Zhao et al, 2017;Zhu et al, 2018b). These modifications not only increase surface adsorption sites, but also change surface charge and functional group characteristics that regulate Cr(VI) adsorption and reduction dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pristine biochars, acquired from direct biomass pyrolysis, often have relatively low adsorptive and reductive ability for Cr(VI), but these properties are dependent on biomass feedstock and pyrolysis temperature (Dong et al, 2011;Jin et al, 2016;Zhang et al, 2018). Thus, specific activation processes, such as surface functionalization, molecular grafting, ultraviolet irradiation and ball milling, have been used to enhance the Cr(VI) removal performance of biochars (Peng et al, 2018;Zhang et al, 2019b;Zhao et al, 2017;Zhu et al, 2018b). These modifications not only increase surface adsorption sites, but also change surface charge and functional group characteristics that regulate Cr(VI) adsorption and reduction dynamics.…”
Section: Introductionmentioning
confidence: 99%
“… Adsorbent Q max (mg g −1 ) pH Conc. (mg L −1 ) BET (m 2 g −1 ) T (K) References MNA-S 15.6 2.5 20–50 152.6 298 46 MNA-L 11.1 2.5 20–50 34.4 298 46 microalgal based materials 25.19 2 1–10 295 47 UV-modified biochar 20.04 Natural pH 20 298 48 Melia azedarach wood magnetic biochar 25.27 3.0 5–200 5.219 298 48 Oak wood char 4.62 2.0 1–100 1–3 298 22 Oak bark char 4.61 2.0 1–100 1.88 298 22 Astragalus mongholicus magnetic biochar 23.85 …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that UV treatment enhances polar functionalities like carboxyl groups and reduces the pH of BC, leading to a reduced effect in raising soil pH (Figure 6) (Peng et al., 2018; Zhang et al., 2021). Other physical modification methods such as ultrasonic and microwave modifications are still uncertain because no researchers have investigated their potential effects on saline‐alkali soil remediation.…”
Section: Modification Methods and Mechanisms Of Bc For Saline‐alkali ...mentioning
confidence: 99%